(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
2,3-Trimethylenepyrido[2,3-d]pyrimidin-4-one reacts with the Vilsmeier reagent to give α-Dimethylaminomethylidene derivative. X-ray structure analysis has been carried out for the product of the reaction.